Peningkatan Kemampuan Menulis Deskripsi Bahasa Inggris Melalui Strategi Pembelajaran Partisipatif - Millah, Syaeful (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The aim of this research is to improve English descriptive writing skill through participatory strategy. This research is an action research in SMP Negeri 1 Gempol for students in the first grade.The data of this research was found from students in that class amounted to 38 students.The obtained data is qualitative and quantitative data. The qualitative data of this research is the student learning process of descriptive writing through participatory strategy in SMP Negeri 1 Gempol for students in first grade.The quantitative data is scores or results of students’ English writing test, both before or after learning process through participatory strategy.The obtained data indicates students’ improving English descriptive writing skill through participatory strategy. The result indicates that the use of participatory strategy is applied well.This research can be used by teachers in the school who want to improve their students’ English writing skill. This research can also give some benefits for the other students who want to make an action research